Facile non thermal plasma based desorption of self assembled monolayers for achieving low temperature and low pressure Cu–Cu thermo-compression bonding. Issue 125 (8th December 2015) - Ghosh, Tamal; Krushnamurthy, K.; Panigrahi, Asisa Kumar; Dutta, Asudeb; Subrahmanyam, Ch.; Vanjari, Siva Rama Krishna; Singh, Shiv Govind
Abstract : This paper reports Self Assembled Monolayer (SAM) of propanethiol desorption assisted low temperature, low pressure Cu–Cu thermo-compression bonding, a technique which could be applied to developing next generation heterogeneous smart devices. Abstract : This paper reports Self Assembled Monolayer (SAM) of propanethiol desorption assisted low temperature, low pressure copper to copper (Cu–Cu) thermo-compression bonding, a technique which could potentially open up a whole new platform for developing next generation heterogeneous smart devices using 3D integrated circuit technology. Thiolated self assembled monolayers protect a freshly deposited copper surface from oxidation and other contamination. Removal of this SAM layer just prior to bonding would potentially bring down temperature and pressure thus rendering the process CMOS compatible. This paper focuses on using Non-Thermal Plasma (NTP) desorption, which is a simple, robust, room temperature technique for desorbing SAMs. The desorption was carried out in an indigenous chamber specifically designed for this purpose. Thermo-compression bonding post desorption resulted in a very good quality bonding with a bond strength of 132 MPa, performed at a relatively low temperature of 200 °C and a low pressure of 5 bar.